High-dose allopurinol prolongs time to exercise-induced ischaemia in chronic stable angina. (22nd September 2015) - Noman, A; Ang, D; Lang, CC; Struthers, AD
Abstract : Background: Experimental work has shown that allopurinol, a xanthine oxidase inhibitor, improves "mechano-energetic uncoupling" of the myocardium in heart failure. This means that allopurinol reduces myocardial oxygen demand for a given stroke volume. Such an effect might be of value in angina pectoris. In addition, allopurinol has been shown to improve endothelial function and reduce oxidative stress in patients with coronary artery disease. This study was designed to investigate whether allopurinol had any anti-ischaemic or anti-anginal effects in patients with chronic stable angina. Method: In a double-blind, placebo-controlled, crossover trial, 60 eligible patients with chronic stable angina and angiographically confirmed coronary artery disease were randomly assigned to receive either placebo or allopurinol (600 mg/day) for 6 weeks and were then crossed over to the alternative therapy for a further 6 weeks. The main outcome measurements were changes in total exercise time (TET), time to onset of angina symptoms (Tsym) and time to ST depression (TST) on the exercise treadmill test using the Bruce protocol. These measures were assessed at baseline and after each treatment period. Results: The median baseline TET was 301 s (interquartile range (IQR) 251–446), Tsym was 233.5 s (IQR 188–381) and TST was 232 s (IQR 182–379). Allopurinol increased TET by 53.7 s versus −7.1 s for placebo (p<0.001), Tsym by 49.5 s versus 9.5 s for placebo (p = 0.01) and TST by 48.5 s versus 14.5 s for placebo (p<0.001). Conclusion: In patients with chronic stable angina, allopurinol (600 mg/day) improves TET and Tsym and to ischaemia during exercise. These results support the use of allopurinol as a novel anti-ischaemic agent in patients with angina pectoris. They also point towards a potential role for the enzyme xanthine oxidoreductase in the pathophysiology of chest pain in angina pectoris.